Annual Wheat Newsletter. Volume 62 - Raupp, W. J. (Dept. of Plant Pathology. Kansas State University, 2016)
The Annual Wheat Newsletter is edited by W.J. Raupp and published by the Wheat Genetic and Genomic Resources Center at Kansas State University. The scope of the Newsletter includes current project activities, cultivar releases, special reports, and publications of wheat researchers worldwide. The Newsletter annually has over 100 contributors from more than 30 countries.
Keywords: Wheat; Genetics; Genomics; Research